Macrolide resistance in Mycoplasma genitalium in Catalonia, Spain: a 1 year prospective study. (19th July 2021) - Lucena Nemirosky, J; Espelt, R; López Grado, E; Sobrino, J; Acera, A; Pérez, J; Jensen, J S; Sánchez-Reus, F; Prim, N
Abstract: Background: Mycoplasma genitalium is an emergent cause of sexually transmitted disease (STD). The first-line treatment is azithromycin, but macrolide resistance is increasing due to mutations in the 23S rRNA gene. Objectives: To determine the rates of M. genitalium infection and macrolide resistance in an area adjacent to Barcelona. Methods: This 1 year prospective study was performed in a heterogenous population that included both low- and high-risk patients. M. genitalium was detected in all specimens sent to our institution for STD detection. Epidemiological and relevant clinical data were collected in the positive cases. Characterization of macrolide-associated resistance was performed by 23S rDNA sequencing. Results: Of the 3540 patients included, 132 (3.7%) were positive for M. genitalium . Another sexually transmitted bacteria was detected in 20.4% of the M. genitalium cases, and Chlamydia trachomatis (11%) was the most frequently co-detected microorganism. Only 61.4% of patients received an adequate initial treatment against M. genitalium . The test of cure (TOC) was performed in 42% of patients, and therapeutic failure was detected in 10 cases. The rate of macrolide resistance was 12.6% and the most prevalent mutation was A2058G. There was an association between macrolide resistance and a previous history of M. genitalium detection ( P < 0.001). Conclusions: Our results support the contribution of the previous use of macrolides in resistant strains. Given the difficulties in performing TOC in all patients, the inclusion of macrolide resistance in the detection test should be mandatory.